ARV-825 Demonstrates Antitumor Activity in Gastric Cancer via MYC-Targets and G2M-Checkpoint Signaling Pathways - Liao, Xinmei; Qian, Xiaoqing; Zhang, Zimu; Tao, Yanfang; Li, Zhiheng; Zhang, Qian; Liang, Hui; Li, Xiaolu; Xie, Yi; Zhuo, Ran; Chen, Yanling; Jiang, You; et al. (Frontiers in Oncology, 2021)
Objective: Suppression of bromodomain and extra terminal (BET) proteins has a bright prospect to treat MYC-driven tumors. Bromodomain containing 4 (BRD4) is one of the BET proteins. ARV-825, consisting of a BRD4 inhibitor conjugated with a cereblon ligand using proteolysis-targeting chimera (PROTAC) technology, was proven to decrease the tumor growth effectively and continuously. Nevertheless, the efficacy and mechanisms of ARV-825 in gastric cancer are still poorly understood. Methods: Cell counting kit 8 assay, lentivirus infection, western blotting analysis, Annexin V/ propidium iodide (PI) staining, RNA sequencing, a xenograft model, and immunohistochemistry were used to assess the efficacy of ARV-825 in cell level and animal model. Results: The mRNA expression of BRD4 in gastric cancer raised significantly than those in normal tissues, which suggested poor outcome of patients with gastric cancer. ARV-825 displayed higher anti-cancer efficiency in gastric cancer cells than OTX015 and JQ1. ARV-825 could inhibit cell growth, inducing cell cycle block and apoptosis in vitro. ARV-825 induced degradation of BRD4, BRD2, BRD3, c-MYC, and polo like kinase 1 (PLK1) proteins in four gastric cancer cell lines. In addition, cleavage of Caspase 3 and poly ADP-ribose polymerase (PARP) was elevated. Knockdown or overexpression CRBN could increase or decrease, respectively, the ARV-825 IC50 of gastric cancer cells. ARV-825 reduced MYC and PLK1 expression in gastric cancer cells. ARV-825 treatment significantly reduced tumor growth without toxic side effects and downregulated the expression of BRD4 in vivo. Conclusions: High mRNA expression of BRD4 in gastric cancer indicated poor prognosis. ARV-825, a BRD4 inhibitor, could effectively suppress the growth and elevate the apoptosis of gastric cancer cells via transcription downregulation of c-MYC and PLK1. These results implied that ARV-825 could be a good therapeutic strategy to treat gastric cancer.